FAKTOR-FAKTOR YANG MEMPENGARUHI LABA PADA LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN MENGWI KABUPATEN BADUNG - NI GUSTI AYU PUTRI NURYATI (GANEC SWARA, 2023)
This study aims to determine the effect of simultaneously or partially the amount of credit (X 1 ), savings (X 2 ) and capital (X 3 ), on profit (Y). This study took place in the LPD, Mengwi District, Badung Regency. The data used in this research is secondary data. Data analysis was performed using multiple linear regression method. The results of data analysis show that the amount of credit, savings and capital simultaneously has a significant effect on LPD profits in Mengwi District, Badung Regency. The variable amount of credit, savings and capital partially has a positive and significant effect on LPD profits in Mengwi District, Badung Regency